2016
DOI: 10.2196/jmir.5969
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Ecological Momentary Assessment Tool (devilSPARC) for Nutrition and Physical Activity Behaviors in College Students: A Validation Study

Abstract: BackgroundThe majority of nutrition and physical activity assessments methods commonly used in scientific research are subject to recall and social desirability biases, which result in over- or under-reporting of behaviors. Real-time mobile-based ecological momentary assessments (mEMAs) may result in decreased measurement biases and minimize participant burden.ObjectiveThe aim was to examine the validity of a mEMA methodology to assess dietary and physical activity levels compared to 24-hour dietary recalls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(133 citation statements)
references
References 36 publications
3
125
0
Order By: Relevance
“…These options were developed based on formative work by Laska et al with college students, which identified common food groups consumed: 1) cookies and sweetened baked goods, 2) candy and gummy fruit snacks, 3) salty snacks, 4) fruits and vegetables, 5) frozen desserts, 6) non-milk dairy products, 7) entrees, 8) cereals and grains, and 9) fried side dishes [ 40 ]. These food groups were adapted to after our pilot with first-year college students [ 41 ]. Participants could select more than one food choice.…”
Section: Methodsmentioning
confidence: 99%
“…These options were developed based on formative work by Laska et al with college students, which identified common food groups consumed: 1) cookies and sweetened baked goods, 2) candy and gummy fruit snacks, 3) salty snacks, 4) fruits and vegetables, 5) frozen desserts, 6) non-milk dairy products, 7) entrees, 8) cereals and grains, and 9) fried side dishes [ 40 ]. These food groups were adapted to after our pilot with first-year college students [ 41 ]. Participants could select more than one food choice.…”
Section: Methodsmentioning
confidence: 99%
“…Food items recorded in the dietary recall were then converted to nutrients based on the food composition tables (31) . Participants whose dietary recall had extreme values of energy intake were excluded; thus, the final analysis included adults (aged 19 years or older) whose total energy intake ranged from 2092 to 20 920 kJ/d (500 to 5000 kcal/d; n 4508), a range commonly applied in observational studies to exclude extreme values of energy intake (32)(33)(34) .…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…More specifically, we agree with defining mEMA as "the use of mobile computing and communication technologies for the ecological momentary assessment of health and lifestyle behaviors". As an example, some researchers have combined mHealth and EMA methodologies to study alcohol, tobacco and drugs consumption (106), depression and anxiety (107), eating disorders and obesity (108), or nutrition and PA behaviors (109). Thus, mEMA methodology can facilitate monitoring of healthy lifestyles under both subjective and objective perspectives, using tools such as written diaries or self-reports on a touch screen, messages on social networks, and motion or physiological sensors, all managed through smartphone apps (7,110).…”
Section: Discussionmentioning
confidence: 99%